Penentuan Metode Pengujian Kadar air dan Percambahan Banih sawo Kecik - Dede J Sudrajat; Eliya Suita (Jurnal Pemuliaan Tanaman Hutan, 2009)
Standard method in physical and physiological quality testing is very imprortant to support a controlling system of distributed seed quality by certification that will provide a guarantee to prosedure; distributor, and user. Five seed lot of sawo kecil (Manilkara kauki) from Mokmer (Bali), Benoa (Bali), Lombar (Lombok), Kaliurang (Yogyakarta) and Alas Purwo (Banyuwangi) were used to identify the best method for moisture content and germination testing. Completely randomized design was applied to determine the best method for moisture content testing. The treatments in selection of the appropriateMethod were oven method on the temperature 130 – 133 oC (1-,2-,3-, and 4 hours) and temperature 103 ± 20C (16-,18-,20-,22-, and    haours). The selection of germination method used completely randomized design with 3 factors of treatment, i.e. sowing media, pretreatment, and germination condition. The result showed that oven method at temperature 103 +_20C for 24 hours and at temperature 130-1330 C 4 hours provided the best result for seed moisture content testing. For seed germination testing, seeds sowed on the sand media with drying-wetting pretreatmen for 3 days on the germination box covered by transparent plastic provided the best germination capacity and speed toward 5 seed lots. The methods can be considered to be appied in the testing of moisture conten and germination of sawo kecik seeds.